2019
DOI: 10.4204/eptcs.305.10
|View full text |Cite
|
Sign up to set email alerts
|

Query Learning Algorithm for Residual Symbolic Finite Automata

Abstract: We propose a query learning algorithm for residual symbolic finite automata (RSFAs). Symbolic finite automata (SFAs) are finite automata whose transitions are labeled by predicates over a Boolean algebra, in which a big collection of characters leading the same transition may be represented by a single predicate. Residual finite automata (RFAs) are a special type of non-deterministic finite automata which can be exponentially smaller than the minimum deterministic finite automata and have a favorable property … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In particular, an extension of L * , termed MAT * , to learn SFAs was provided in [AD18] which proved that SFAs over an algebra A can be efficiently learned using MAT * if and only if the underlying algebra is efficiently learnable, and the size of disjunctions of k predicates does not grow exponentially in k. 12 From this it was concluded that SFAs over the following underlying algebras are efficiently learnable: Boolean algebras over finite domains, equality algebra, tree automata algebra, and SFAs algebra. Efficient learning of SFAs over a monotonic algebra using mqs and eqs was established in [CDYS17], which improved the results of [MM14, MM17] by using a binary search instead of a helpful teacher.…”
Section: Query Learningmentioning
confidence: 83%
“…In particular, an extension of L * , termed MAT * , to learn SFAs was provided in [AD18] which proved that SFAs over an algebra A can be efficiently learned using MAT * if and only if the underlying algebra is efficiently learnable, and the size of disjunctions of k predicates does not grow exponentially in k. 12 From this it was concluded that SFAs over the following underlying algebras are efficiently learnable: Boolean algebras over finite domains, equality algebra, tree automata algebra, and SFAs algebra. Efficient learning of SFAs over a monotonic algebra using mqs and eqs was established in [CDYS17], which improved the results of [MM14, MM17] by using a binary search instead of a helpful teacher.…”
Section: Query Learningmentioning
confidence: 83%
“…There already exists substantial literature on learning restricted forms of SFAs [GJL10, MM14, ASKK16, MM17, CDYS17], as well as general SFAs [DD17,AD18], and even nondeterministic residual SFAs [CHYS19]. For other types of automata over infinite alphabets, [HSM11] suggests learning abstractions, and [She19] presents a learning algorithm for deterministic variable automata.…”
Section: Introductionmentioning
confidence: 99%